Treatment of peptic esophageal stricture with combined fundic patch-fundoplication. - Hollenbeck, J I (1975)
Forty-five patients treated for peptic esophageal stricture by combined fundic patch-fundoplication are reviewed. The operation afforded an acceptable result in 87% of the patients. There has been no operative mortality. The stricture represents transmural fibrosis of the distal esophagus. The fibrosis interferes with the physiologic function of the LES preventing receptive relaxation. This, however, does not affect the postoperative ability to swallow.